Diversidade genética de 43 genótipos de Coffeacanephora; e implicações do aumento de temperatura e déficit hídrico ao Coffea spp. - Dubberstein, Danielly (2019)
Chapters 1, 2 and 3 have the objective of studying the genetics of the 43 unpublished Coffea canephora genotypes through the stomatal and plant leaf morphological characteristics, as well as the choice of a mathematical model to determine the leaf area developed from linear of sheet. In chapter 1 the study of the stomatal characteristics was carried out, determining: epidermal cell count and number of stomata, polar and equatorial diameter measurement, density estimation, stomatal area index, stomatal index and stomatal functionality. Data were submitted to analysis of variance, grouped by the hierarchical method Unweighted Pair Group Method using Arithmetic Averages (UPGMA); Pearson's linear correlation and principal component analysis in Biplot were also performed. Differences were observed among the 43 genotypes confirming the existence of genetic variability; the grouping method distinguished them into six groups; correlations with different levels of significance occurred among the parameters; plant height, distance internodes and leaf area correlate positively, showing that they can be associated with stomatal characteristics. In chapter 2 we estimated: length, number of nodes and distance between nodes of plagiotropic and orthotropic branches; plant height; cup diameter; length, width and actual leaf area of leaves in two evaluations. The data were submitted to analysis of variance, grouped by the Tocher optimization method and by the UPGMA hierarchical method, made to the analysis of Pearson's linear correlation and main components in Biplot. Significant differences were found among the 43 genotypes, forming six groups by the Tocher method and five groups by UPGMA, evidencing the existing genetic variability. Pearson's correlation provided values with different levels between characteristics, as evidenced by principal component analysis. In Chapter 3, the length of the midrib (L) and maximum leaf blade width (W) and leaf area (LA) of the 43 genotypes were measured manually. From L, W, LA and LW, Pearson correlation analyzes were performed, grouped by the Tocher optimization method, all combinations were tested by linear models according to the existing parameters and the values of R2 and BIC were just for h mo l. Est bl sh th qu t ons ons r n th p r m t rs ß0 n ß1. Th 43 genotypes were divided into three groups by the Tocher method and one group with 41 genotypes. Larger correlations occurred between products L and W (LW) and LA, followed by W and LA. Therefore, LW estimates the leaf area satisfactorily, but the variable width can be adopted due to the greater ease of measurement in the field. The equations generated considering the two variables were significant and the cross validation confirmed the adjustment. The objective of chapter 4 was to evaluate the impacts of individual and joint heat and drought stresses in coffee trees. Leaf parameters related to stomatal characteristics, gas 4 exchange, chlorophyll a fluorescence, thylakoidal electron transport, membrane permeability and activities of photosynthesis enzymes. In addition, chapter 5 aimed to identify mechanisms of response/acclimation of plants to heat and dry stress conditions, where they were evaluated the photoinhibition of PSII, the activities of the enzymes Ascorbate Peroxidase (APX), Glutathione Reductase (GR), Superoxide Dismutase (Cu, Zn-SOD) as well as Ascorbate (ASC) content, heat shock enzyme (HSP70), photosynthetic pigments and malondialdehyde (MDA). It was observed that well-watered plants maintained good photosynthetic performance with temperature increase, presenting changes only at 39/30 °C in CL153 and Icatu from 34/28 °C as well as there was increase of Fo and decrease in Fv/Fm (Pn, Gs, E, Ci, iWUE and Amax), and the effect of heat on these plants was more evident at 42/30 °C only in Icatu. The joint imposition of stressors aggravates the situation, although some parameters have not been modified (for example: Pn and Amax in CL 153). The activity of the photosynthesis and photosynthetic enzymes was reduced with the simultaneous imposition of drought and heat. The photosynthetic structures in general, and the photosystems in particular, have been impacted, but the negative effects have been mitigated by the reinforcement of protective mechanisms. These are reflected in the increases in the values of Y(NPQ) (unregulated energy dissipation) and qN (sustained heat dissipation photoprotective), HPS70, and some photosynthetic pigments such as Neaxanthin, Anteraxanthin, Zeaxanthin, DEPS and Lutein, as well as increased APX, SOD and GR activity (which act in the removal of reactive oxygen species). The MDA content was increased only at 42/30 °C, confirming the membrane lipid peroxidation, but evidencing the leaf thermotolerance in the coffee trees at temperatures well above the optimum. In addition, a considerable recovery was observed for several parameters after reestablishment of the normal water and temperature conditions, confirming the resilience of the coffee trees